2010
DOI: 10.1159/000313038
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of Growth Hormone in Adult Hemodialysis Patients: Results from a Randomized Controlled Trial

Abstract: Background/Aims: The high morbidity and mortality rates in hemodialysis (HD) patients are due, at least in part, to their increased risk for cardiovascular diseases (CVD). This prospective study evaluated the effect of growth hormone (GH) on a number of CVD risk markers in adult patients on HD. Methods: 139 HD patients were randomized to one of three GH doses or to placebo. Change from baseline in lean body mass (LBM), CVD risk markers (e.g. lipid profile, plasma homocysteine, inflammatory markers, blood press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 110 publications
(61 reference statements)
3
5
0
Order By: Relevance
“…Also, no symptoms of OCD, PTSD, social phobia, specific phobias, or somatization disorder were detected after assessment using SCIDI scale. These findings agreed with the study done by Kober et al [12], which was done on 100 patients 50 of them were cases of ESRD and the other 50 were control group, using HAM scale (Hamilton Rating scale) for anxiety and BDI (Beck Depression Inventory) for depression as he found that the prevalence of psychiatric illness among them was 44%, 40% of patients suffered from depression, while the percentage of patients suffering from anxiety disorders were 42%. These findings agree with Garcia et al [13], who found that (68.1%) of them had score equal to or more than 7, which suggested depression.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Also, no symptoms of OCD, PTSD, social phobia, specific phobias, or somatization disorder were detected after assessment using SCIDI scale. These findings agreed with the study done by Kober et al [12], which was done on 100 patients 50 of them were cases of ESRD and the other 50 were control group, using HAM scale (Hamilton Rating scale) for anxiety and BDI (Beck Depression Inventory) for depression as he found that the prevalence of psychiatric illness among them was 44%, 40% of patients suffered from depression, while the percentage of patients suffering from anxiety disorders were 42%. These findings agree with Garcia et al [13], who found that (68.1%) of them had score equal to or more than 7, which suggested depression.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, the scores reflect the respondents' satisfaction with the aspects of life as they value. Total scores may be classified in three levels: desirable (score: 20-30), relatively desirable (score: [10][11][12][13][14][15][16][17][18][19], and unfavorable (score: 0-9).…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…Part of the ghrelin’s cardioprotective activity is growth hormone-releasing hormone (GHRH) mediated [30], whereas the second part is independent of GH secretion and likely to involve binding to cardiovascular receptors, a process that is upregulated during ischemia reperfusion [31]. In clinical studies in MHD population, MK-0677, an oral ghrelin receptor agonist, maintained normal GH secretion and increased LBM [32], while GH treatment had a predominantly beneficial effect on cardiovascular risk markers [33, 34]. When ghrelin increases GHRH release from hypothalamic explants, obestatin only reduces the ghrelin-induced increase of GHRH release [29].…”
Section: Discussionmentioning
confidence: 99%
“…Several other groups [48,49,50] have also investigated changes in markers of nutrition as protein calorie malnutrition, which remains one of the most important predictors of mortality in CKD patients, whether they are dialysis dependent or not [51]. A few studies have reported a possibility of reversing this morbidity and mortality following improvement of the malnutrition state [52,53,54].…”
Section: Evidence For the Use Of Gh In Ckdmentioning
confidence: 99%
“…However, there were no changes in nutritional indices. To investigate the impact on LBM, investigators [48] randomized 139 patients to receive three different doses of GH infusion or placebo. GH doses included 0.02, 0.035 and 0.050 mg/kg/day for 6 months after dialysis.…”
Section: Evidence For the Use Of Gh In Ckdmentioning
confidence: 99%